Challenges in distributed leadership: evidence from the perspective of headteachers. Issue 6 (8th August 2016) - Tahir, Lokman Mohd; Lee, Sui Liang; Musah, Mohammed Borhandden; Jaffri, Hadijah; Said, Mohd Nihra Haruzuan Mohamad; Yasin, Mohd Hanafi Mohd
Abstract : Purpose: This study investigates the issues and challenges faced by headteachers in practicing the suggested distributed leadership approach in three primary schools to their middle layer leaders. Design/methodology/approach: The study employed a case study design and data were collected through semi-structured interviews. A total of three headteachers were interviewed in examining and exploring challenges within the distributed leadership practices. The transcripts from the semi-structured interviews formed the basis of the findings. Findings: The findings suggest that senior teachers lack confidence in making decisions and rely on the consent from headteachers even though they are empowered to make their own decisions. Another significant issue faced by headteachers when distributing their leadership is the ability, expertise, experience, and willingness of teachers to hold leadership roles and responsibilities. Originality/value: The results are important since there have been few empirical studies on the issues and challenges faced by headteachers in practising distributed leadership approach in primary schools in the context of Malaysia. This initiative sidelines the traditional school leadership approach which emphasises on the accountability of headteachers as the sole school leader.